TINJAUAN YURIDIS HAK DAN KEWAJIBAN AYAH TERHADAP ANAK KANDUNG SETELAH PERCERAIAN (Di Pengadilan Agama Selong Lombok Timur ) - Fahrurrozi Fahrurrozi; Chintya Dewanta; Imawanto Imawanto; Edi Yanto; Hamdi Hamdi; Yulias Erwin; Sarudi Sarudi; Tin Yuliani; Aesthetica Fiorini Mantika (Media Keadilan: Jurnal Ilmu Hukum, 2023)
This study aims to find answers to the problems formulated, namely to find out the implementation of the rights and obligations of fathers towards biological children after a divorce case study at the Agam Selong Court. This research uses a type of normative legal research using the statute approach, case approach and conceptual approach. The conclusions from this study indicate that divorce will not eliminate or abort the obligations of parents towards their children, that the obligations of parents are still the same, whether there is a divorce or not.